La fenomenología personalista de Francisco Leocata y la teoría de la interacción de Shaun Gallagher - Franck, Juan F. (Sapientia, 2022)
The article outlines an approximation between the personalist reading of phenomenology developed by Francisco Leocata, and Shaun Gallagher's recent Interaction Theory, in the field of philosophy of action. First, it presents in broad strokes the central themes that guide Leocata's position, fundamentally his reading of the phenomenological, eidetic, and transcendental reductions, as well as his innovative vital reduction. Then he highlights the greater explanatory capacity of Interaction Theory compared to theories of mind to explain human action, by placing the accent on the relational nature of the action. The final part proposes some conclusions from the encounter between both conceptions, highlighting both important coincidences and differences, due to a different level of analysis. The two conceptions reinforce the conviction that the alternative "irreducibility or interaction" is not valid, but that both occur together, although their analysis responds to different methods. One can also speak of an analogy of intersubjectivity.